Desain Sistem Keamanan Distribusi Data Dengan Menerapkan XML Encryption Dan XML Signature Berbasis Teknologi Web Service - Widodo, Slamet; Eko Sediyono, Eko; Suhartono, Suhartono (JSINBIS (Jurnal Sistem Informasi Bisnis), 2011)
Development of information technologies is often misused by an organization or a person to take criminal acts, such as the ability to steal and modify information in the data distribution for evil criminal purpose. The Rural Bank of Boyolali is conducting online financial transactions rather intensively, thus it requiring a security system on the distribution of data and credit transactions for their customer among branches offices to head office. The purpose of this study was to build a security system in credit transactions in Rural Bank of Boyolali for their customers among branches offices to head office. One way in protecting data distribution was used XML encryption and XML signature. The application of encryption technique in XML and digital signature in XML by using web service by using the AES (Advanced Encryption Standard) and RSA (Rivest-Shamir-Adleman) algorithms. This study was resulted the SOAP (Simple Object Access Protocol) message security system, with XML and WSDL (Web Services Description Language), over HTTP (Hypertext Transfer Protocol) to protect the customers’ credit transactions from intruders. Analysis of examination indicated that the data size (bytes) transferred as results of uncompressed XML encryption were larger than compressed XML Encryption, which leads to significant changes between the data transferred that was the processing time of the compressed data was faster than uncompressed XML encryption.